Step-by-step explanation: if eq. has equal root then, D=0 b²-4ac=0 {2(k+2)}²-4×1×9k=0 4(k²+4k+4)-36k=0 4k²+16k+16-36k=0 4k²-20k+16=0 4(k²-5k+4)=0 k²-5k+4=0 k²-4k-k+4=0 k(k-4)-1(k-4)=0 (k-1)(k-4)=0 either k-1=0 or k-4=0 k-1=0 k-4=0 k=1 k=4 hence k=1 or 4 #666 Reply

Step-by-step explanation:if eq. has equal root then,

D=0

b²-4ac=0

{2(k+2)}²-4×1×9k=0

4(k²+4k+4)-36k=0

4k²+16k+16-36k=0

4k²-20k+16=0

4(k²-5k+4)=0

k²-5k+4=0

k²-4k-k+4=0

k(k-4)-1(k-4)=0

(k-1)(k-4)=0

either k-1=0 or k-4=0

k-1=0 k-4=0

k=1 k=4

hence k=1 or 4

#666